Development of an RF listening mode on the TIGER-3 FPGA platform - van Zyl, Willem Francois (Department of Electrical Engineering, 2021)
High frequency (HF) radars have many critical applications due to the effects that physical media have on the wave's propagation. The diffraction of HF radio waves in the ionosphere allows for long range communication and radar operation. Waves travel over the horizon where they may be reflected off large scatterers such as ships, or monitor sea states over large oceanic surface areas. Furthermore, the ionosphere provides key information on solar weather. Monitoring RF reflections from the ionosphere (specifically at the polar regions) is of great importance to the scientific community. The use of the HF (3-30 Mhz) has been greatly simplified for radar transceivers in recent decades. Digital hardware can sample and process information fast enough to eliminate the need for conventional analogue down-converters. The result is an increase in sensitivity, signal to noise ratio and design simplicity. The primary advantage of digital radars is versatility. The ability to change parameters and even modes of operation means that digital radars have become more common, and have replaced or been partly integrated into most of their analogue counterparts. The SuperDARN is a network of ionosphere monitoring radars that have been in operation since the 1980s. Since its inception it has undergone multiple improvements and served the scientific community well. The 4th South African National Arctic Expedition (SANAE IV) makes use of a digital radar platform based on the third generation TIGER-3 FPGA boards. The highly adaptable nature of the transceivers provide a host of secondary applications and improvements to its analogue predecessors. The system is however not in a state that supports further development. Currently the system is programmed for a set mode of operation without access to the source software. This work details the design and implementation process followed to bring the TIGER-3 system to a state that will support further development. In this state, peripheral interfaces are designed and implemented to allow for a listening mode of operation. In this mode, the radar samples a signal from an antenna and effectively communicates the data to a personal computer via an Ethernet link. To achieve these outcomes; FPGA code (written in Verilog) was developed to implement IQ downconversion, digital filtering, and a client interface for the Ethernet link. The features were tested by recording and analysing digital outputs from the platform, and finally, by recording signal information obtained through the Ethernet interface. Supporting literature will lay the groundwork for future projects to build on the base layer implementation; with the hope of redesigning the current SuperDARN implementation in the future. Further improvements to the current system could include a range of scanning patters and multi-frequency operation.